Overview of L- to H-mode transition experiments at ASDEX Upgrade. (6th December 2022) - Plank, U; McDermott, R M; Birkenmeier, G; Bonanomi, N; Cavedon, M; Conway, G D; Eich, T; Griener, M; Grover, O; Schneider, P A; Willensdorfer, M; ,
Abstract: This paper presents an overview of results from L–H transition experiments that were performed at ASDEX Upgrade (AUG) with the aim of identifying the underlying mechanisms leading to H-mode confinement. With a broad variety of experiments and new diagnostic techniques, as well as modeling efforts, AUG has contributed substantially to improving our understanding of the L–H transition over the past years. In this review, the important roles of the ion heat channel and the edge radial electric field ( E r ) in the L–H transition physics are brought into context with known dependencies of the H-mode power threshold ( P L H ), such as the impact of wall material, magnetic perturbations, and the magnetic configuration. Furthermore, experimental and theoretical results obtained at AUG on the L-mode edge turbulence are connected to the mean-field E r and its related shear flow. This led to a deeper understanding of the I-phase plasma regime, has resolved the so-called isotope effect of P L H, and led to the development of a semi-analytical model that can describe AUG's experimental observations of the L–H transition together with the L- and H-mode density limits.